Effects of anaerobic digestion pretreatment on the pyrolysis of Sargassum: Investigation by TG-FTIR and Py-GC/MS. (1st September 2022) - Wang, Zhi; Che, Yuechi; Li, Jian; Wu, Wenzhu; Yan, Beibei; Zhang, Yingxiu; Wang, Xutong; Yu, Fan; Chen, Guanyi; Zuo, Xiaoyu; Li, Xiujin
Graphical abstract: Highlights: Anaerobic digestion provides an alternative pretreatment for pyrolysis process. The Sargassum structure was loosened due to the use of biodegradable fractions. Mild anaerobic digestion pretreatment facilitated the release of gaseous product. The relative content of N-compounds and hydrocarbons was enhanced with pretreatment. Abstract: Anaerobic digestion was tentatively used as a pretreatment to change the pyrolysis characteristics of Sargassum in this study. The physicochemical properties of Sargassum with different anaerobic digestion durations were investigated. With the increasing the anaerobic digestion duration from 0 to 21 days, the content of extract and cellulose decreased from 37.5 wt% and 12.63 wt% to 27.82 wt% and 4.73 wt%, respectively. While the content of lignin increased from 9.99 wt% to 14.69 wt%. The apparent structure of Sargassum was altered due to changes in chemical composition, which increased the fiber crystallinity and specific surface area. In addition, the effects of anaerobic digestion durations on the gaseous and liquid products of pyrolysis were analyzed by TG-FTIR and Py-GC/MS, respectively. The thermal stability of Sargassum was enhanced due to the consumption of organic matter during anaerobic digestion. The temperatures of weight loss peak for P1-P4 were 326.83, 335.92, 328.80 and 322.75 °C in the devolatilization step, and the final residual mass percentages of Sargassum digestate (digested for 0, 7, 14 and 21 days) were 37.39, 44.61, 48.89 and 49.29%, respectively. Due to the consumption of biodegradable fractions, the structure of Sargassum was loosened. Thus, mild anaerobic digestion pretreatment facilitated the release of functional groups and gases, whereas excessive consumption of some biodegradable fractions might reduce the corresponding gaseous product. The selectivity of bio-oils composition was also altered by anaerobic digestion pretreatment. The relative content of N-compounds and hydrocarbons was enhanced, and the formation of O-compounds was inhibited with anaerobic digestion pretreatment. This study proved that anaerobic digestion pretreatment could alter the composition and structure of the biomass, which varied the thermal-stability and thus influenced the quality of the pyrolytic products. This new attempt is expected to provide an alternative pretreatment for pyrolysis process.